State of the Art of the Marine Non-Indigenous Flora and Fauna in Slovenia - L. LIPEJ; B. MAVRIC; M. ORLANDO-BONACA; A. MALEJ (Mediterranean Marine Science, 2012)
Authors provide the state of knowledge on marine non-indigenous species in waters off Slovenia. According to published records and authors unpublished data at least 15 non-indigenous species were up to date recorded in the Slovenian part of the Adriatic sea. Eleven species were considered as established and four species as casual. The vectors of introduction are various, comprising Lessepsian migration, mariculture and shipping. The majority of non-indigenous taxa were recorded in the mediolittoral belt and coastal lagoons. The low number of non-indigenous species so far recorded in the Slovenian part of the Adriatic sea could be explained by various factors. Among them, the most reasonable are the lack of scientific attention, the small proportion of Slovenian Sea and low winter temperatures, which represents a physiological barrier for the survival of newcomers. The number of recorded species is far from being satisfactory. Therefore, we expect that the list of non-indigenous species will be enlarged in the nearby future.